Nutritional variables related to gingival health in adolescent girls - Petti S, Cairella G, Tarsitani G (Blackwell Synergy, 2000)
In order to study the nutritional variables associated with gingival health, a case-control study was designed to control strong variables whose effect on gingival status may obscure the potential effect of weaker ones, such as nutrition. Two groups of 27 gingivitis-affected and -unaffected female adolescents were selected.